ENHANCING MATHEMATICS KNOWLEDGE AND PROCESS SKILLS OF STUDENTS WITH LEARNING DIFFICULTIES (Proceedings of International Conference on Special Education, 2017)
Explicit instruction is commonly used for helping students with mathematics learning difficulties. However, some research findings indicate that students’ mastery of conceptual understanding and mathematical process skills was often ignored if this approach was used solely. This research was aimed to investigate the teaching and learning processes during a remedial intervention The intervention was carried out using a mixed instructional approach which combined the perspective of the behaviorists and constructivists. It was expected to enhance the mathematical knowledge and process skills of students. A case study research design was employed. Data was collected and analyzed using a qualitative approach. Results showed that the students were able to improve their mathematics conceptual and procedural knowledge, and mathematical process skills through active interaction and mind-on activities. During the intervention, the teacher used explicit instruction for introduction and followed by student hands-on activities and reflection. The students were actively involved in mathematical processes to make sense and interact with their peers and teacher. However, they still experienced stress when they were required to perform active thinking and demonstration using manipulative and drawing. Wait time and continous support from teacher were needed for them to complete the task. In short, students with mathematics learning difficulties could enhance their mathematics knowledge and process skills through a mixed instructional approach.